Changes in Human Capital: Implications for Productivity Growth in the Euro Area - Guido Schwerdt; Jarkko Turunen (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2007)
The euro area has experienced a sustained decline in labour productivity growth sincethe 1980s. In the economic literature this phenomenon is commonly explained by adecline in capital deepening and lower total factor productivity (TFP) growth. However,the decline in labour productivity growth might partly also reflect a lower contributionof labour quality growth. We present evidence of changes in human capital in a numberof euro area countries based on a fixed-weight index for labour quality growth for boththe employed population and the labour force. We then evaluate the significance ofthese changes for recent developments in productivity growth. Our findings suggest thateuro area labour quality has indeed moderated towards the end of the 1990s, but theimpact on labour productivity growth is small compared to the overall decline in capitaldeepening and total factor productivity growth.
Keywords: E24; J24; O47; 330; Human capital; labour quality; total factor productivity; growth accounting